Sustaining Vision: Competency Modeling to Understand Best Practices for Visual Editors - Smith-Rodden, Martin; Wiley, Marissa (Journalism practice, 2024)
Given the rapidly evolving media ecosystem, the need for excellence in visual storytelling and high-performance among those doing that work has never been more critical. Similarly, practitioners maintain that innovation, entrepreneurial thinking, and novel solutions have never been more needed in media organizations. To help identify best practices, competency modeling is useful to optimize and understand the performance of visual editors. Subject matter interviews with 29 experts in a wide variety of media organizations reveal five competencies: professional, management, leadership, communication, and entrepreneurial. Visual editors noted that experience, technology training, media ethics, socially-supportive communication, and advocating for visual work across departments were key components of their work. Implications for best practices, selection, and training of these specialists are discussed, as well as the entrepreneurial nature of their pivotal role. A key insight for media organizations in need of innovative and entrepreneurial activity is that the change agents they need might be found in-house: among the ranks of visual editors.